Elaboração de planos de aulas para educação física: a percepção discente - Fernanda Carvalho Bittencourt de Oliveira; Maria Teresa Sudário Rocha; Emerson Cruz de Oliveira (Universidade Estadual do Oeste do Paraná, 2018)
The lesson plan is extremely important for teaching activities, but little is discussed about the items that compose it, as well as the practical aspects of its elaboration. The focus of the discussion centered on theoretical foundations that are also indispensable, but which have already been well discussed. The reflection can be broadened, discussing important items for the registration and systematization of the production of knowledge in the area of Physical Education, through the lesson plans. The aim of this study was to compare the perception of beginning and finishing students of a Licentiate degree in Physical Education on the importance of the items that make up a lesson plan, as well as discuss these items considering practical aspects of the elaboration of a lesson plan. This is an exploratory-descriptive study, with a sample of 15 graduates with a real possibility of completing the course (concluding group) and 15 graduates of the first and second periods (beginning group) of both sexes, who received a lined paper with the request to assemble a lesson plan with the content of their choice. For the analysis of the lesson plans, the researchers had at their disposal a list of items previously listed after study. For the statistical analysis of the data, the chi-square test was used, being adopted a level of significance of 5%. The "description of activities" was the only item that all students perceived as important and presented in their plans. The second most remembered item was the setting of objectives for class. The counterpoint was the lack of suggestion of "bibliographical references" and "space for comments and reflections after class". Finally, much still needs to be discussed about the other items that make up a lesson plan that should not be limited to a description of the activities proposed for class.